Methodical approach to the substantiation of the indicators of the anti-aircraft missile system (complex) fire power - Open’ko, Pavlo; Lukyanchuk, Vadym; Nikolaev , Ivan; Dzeverin , Igor; Drannyk, Pavlo (Social Development and Security, 2020)
The results of the research published in the article will be useful for logistic support specialists who are involved in the creation (modernization) of the samples of weapons and military equipment. A methodical approach to substantiating the firepower requirements of a promising anti-aircraft missile system (system) is presented, which provides for the assessment of the components of firepower – search capabilities, firepower and fire resource, taking into account the intensity of the air attack, range and conditions of use of the complex (systems) for each type of goal. A list of indicators of firepower is given, namely, the average time of detection and recognition, the intensity of reconnaissance of targets, the density of the flow of missile launches (rate of fire), the preparation time of the first launch, the probability of hitting a target, and the average consumption of missiles per target. It is shown that the firepower indicators of a promising anti-aircraft missile system (system) at a given level of protection should be determined provided that it is necessary to defeat a selected group of air targets with a probability of not lower than a given level. The requirements for the firepower of a promising anti-aircraft missile system (system) can be substantiated using a complex of mathematical models that provide the opportunity to study scenarios of conflict-information interaction of a promising anti-aircraft missile system (system) and air targets in the form of a simulation machine experiment. It is shown that, based on the simulation results, the indicators of search capabilities, fire performance and fire resource of a promising anti-aircraft missile complex (system), as well as the mathematical expectation of the number of people hit by the whole when the ammunition load of anti-aircraft guided missiles installed on launchers are used, should be determined.